Aerodynamic Characteristics of Flow over Two Unsymmetrical Tandemly Arranged Airfoils – Numerical Simulation. Issue 4 (August 2020) - Abbey, Saransh; Dankhara, Kevin; Senthilkumar, S.
Abstract: There have been many insects having a tandem wing configuration that gives them a major advantage for maneuvering with various desirable speed, such as dragonflies and butterflies, but subsequently have been used for a wider range of applications. So, it is well known that the tandem airfoil arrangement will have better aerodynamic characteristics than those of the single airfoil arrangement. The present work aims at numerically predicting the aerodynamic characteristics of the single airfoil and tandem airfoil arrangements of the Wortmann FX 63-137 airfoil profile at a Reynolds number of 0.5 x 10 6 . The numerical simulations are performed using commercial CFD software, ANSYS-Fluent. Turbulent flows are modeled using the k-ω RANS model with a second-order upwind scheme. The pressure-velocity coupling is done through the SIMPLE algorithm. In the tandem arrangement, airfoils are positively staggered in the flow direction with variable gaps ranging from 0.1m to 0.7m with an increment of 0.2m and the perpendicular distance between the leading edges of two airfoils is fixed at 0.3 m and simulations are performed for a various angle of attacks with a range of 0 to ± 14°. The aerodynamic characteristics of the single and tandem arrangements of the same airfoil are compared and the effect of wake from the primary airfoil on a secondary airfoil at different angles of attack is also studied for the same conditions.